S44 Diagnosis of malignant pleural effusion: can CT findings predict pleural fluid cytology results?. (12th November 2019) - Lu, Q; Mercer, R; Shepherd, G; Castro, O; Varatharajah, R; Thayanandan, A; Hassan, M; Bedawi, E; Mccracken, D; Asciak, R; Addala, D; Tsikrika, M; et al.
Abstract : Introduction: Malignant pleural effusion (MPE) signifies advanced disease and poor prognosis, with median survival ranging from 3 to 12 months. Pleural cytology is a widely used initial investigation for MPE but has a relatively low sensitivity of around 60% 1 . Negative pleural fluid cytology can result in a delay in diagnosis and treatment pathways. Negative CT findings alone cannot out malignancy. Pleural biopsy provides a definitive diagnosis of malignancy in the majority of cases of MPE, 1 but is more invasive and may not be suitable for every patient. Objective: The aim of this retrospective analysis was to assess the relationship between CT findings that are often associated with malignancy, and pleural cytology results. Methods: We performed a retrospective analysis of all patients who had a pleural aspiration between 2015 and 2017 (n=219) with either positive pleural fluid cytology or a malignant pleural biopsy following negative cytology at a UK tertiary hospital. Patients were divided into two groups according to the cytology results. Chi-Square tests were used to analyse the relationship between CT findings and cytology result. Patients with negative pleural fluid cytology who did not go on to have a pleural biopsy were excluded. Results: Of the 219 patients with diagnosed MPE, fluid cytology was positive in 151 (68.9%) patients. The remaining 68 (31.1%) patients had positive pleural biopsy as the initial cytology test was negative. Thoracic lymphadenopathy on CT was associated with positive pleural fluid cytology (odds ratio [OR]=1.82; p=0.042). Pleural nodularity (OR=4.76; p<0.001) and pleural thickening (OR=14.8; p<0.001) on CT were associated with negative pleural fluid cytology. After excluding patients with mesothelioma, pleural nodularity (p<0.001) and pleural thickening (p<0.001) were still associated with negative cytology reports. Conclusions: This study suggests that pleural nodularity and pleural thickening on CT are associated with negative pleural fluid cytology. In patients with such features on CT and suspected MPE, a 'straight to pleural biopsy' approach should be considered. Reference: Hooper C, Lee YCG, Maskell Investigation of a unilateral pleural effusion in adults: British Thoracic Society pleural disease guideline 2010. Thorax 2010;65: ii4-ii17.